2004
DOI: 10.1002/aqc.633
|View full text |Cite
|
Sign up to set email alerts
|

Selecting areas to protect the biodiversity of aquatic ecosystems in a semiarid Mediterranean region using water beetles

Abstract: ABSTRACT1. In this work, carried out in the province of Murcia, a representative semi-arid area of the Iberian Peninsula, water beetles were used as indicators to identify the aquatic ecosystems with the highest interest for conservation. For that purpose, an iterative algorithm of complementarity based on the richness of aquatic Coleoptera was applied. 'Complementarity' refers to the degree to which an area, or set of areas, contributes otherwise unrepresented attributes to a set of areas. This principle was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 26 publications
1
39
0
3
Order By: Relevance
“…As Collinson et al (1995) indicated, the conservation of temporary wetlands should seek to protect all taxa, and micro-crustaceans should be included in future conservative legislation. Moreover, it is important to note that Mediterranean region is considered as a sensitive area to climatic changes (Sánchez-Fernández et al, 2004). Although Mediterranean water bodies are characterized by extreme natural water level fluctuations in response to irregular precipitation patterns (Álvarez-Cobelas et al, 2005), global climatic change is projected to amplify this pattern as a consequence of: i) the increase of temperatures; ii) the elevation of evapotranspiration rates; iii) the diminution of precipitation levels; and iv) the increase of summer droughts (Coops et al, 2003;Angeler, Jurado et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Collinson et al (1995) indicated, the conservation of temporary wetlands should seek to protect all taxa, and micro-crustaceans should be included in future conservative legislation. Moreover, it is important to note that Mediterranean region is considered as a sensitive area to climatic changes (Sánchez-Fernández et al, 2004). Although Mediterranean water bodies are characterized by extreme natural water level fluctuations in response to irregular precipitation patterns (Álvarez-Cobelas et al, 2005), global climatic change is projected to amplify this pattern as a consequence of: i) the increase of temperatures; ii) the elevation of evapotranspiration rates; iii) the diminution of precipitation levels; and iv) the increase of summer droughts (Coops et al, 2003;Angeler, Jurado et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the southern Iberian Peninsula is an area of special interest as it is located in one of the most arid zones of Europe and comprises a wide range of aquatic ecosystems, from freshwater to hypersaline ones (Sánchez-Fernández et al, 2004), which represent an important component of the landscape.…”
Section: Introductionmentioning
confidence: 99%
“…Due to anthropogenic pressure and the specific hydrology and soil morphology (Sánchez-Fernández et al, 2004), karst habitats are particularly endangered. These fragile ecosystems are inhabited by numerous rare and endangered species (Bonacci et al, 2008;Bonacci, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies highlighted the contribution of standing waters to regional freshwater biodiversity (Williams et al, 2003;Picazo et al, 2010) and the usefulness of aquatic Coleoptera as surrogates of biodiversity (Foster et al, 1990;Sánchez-Fernández et al, 2004Guareschi et al, 2012). Therefore, management measures in standing water bodies should consider water beetles as indicators, as they are sensitive species to ecological changes and habitat characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The Iberian Peninsula is a recognized hotspot for biodiversity and more than 500 species of aquatic beetles have been reported in this region. Several authors have suggested the use of aquatic Coleoptera as indicators for monitoring population trends in other groups of aquatic macroinvertebrates and for identifying high biodiversity areas at a regional scale (Foster et al, 1990;Sánchez-Fernández et al, 2004Guareschi et al, 2012). This paper studies the diversity and composition of aquatic Coleoptera assemblages in 24 wetlands protected N o n -c o m m e r c i a l u s e o n l y by the Natura 2000 network of North-western Spain and the influence of environmental variables on the distribution of species, in order to detect differences between the different types of standing water habitats.…”
Section: Introductionmentioning
confidence: 99%